Improving the Process of Teaching Students of a Pedagogical University in Biochemistry Using Kaizen Technology - Myktybekova, Yrza; Zhumagulova, Kalampyr; Digel, Ilya (Universitas Negeri Semarang, 2025)
This study aims to develop and theoretically support an adaptive model for teaching biochemistry in pedagogical universities based on Kaizen and the Plan, Do, Check, and Act (PDCA) continuous improvement cycle, as well as to analyse its adaptability to Kazakhstan’s teacher education system by comparing it to international educational practices. Mixed-methods educational Research and Development was used in the project. Theoretical modelling, pedagogical design, document analysis, a qualitative comparative study of Japan, South Korea, and Singapore, and design-based research were used. Kaizen diaries, reflective student reports, and teacher observation procedures collected qualitative data, while descriptive statistics of students’ learning performance and progress dynamics throughout PDCA cycles included quantitative data. The study created a theoretical model of an adaptive biochemistry course using the PDCA stages to plan didactic material, conduct classes with self-control, reflect on learning outcomes, and adjust content. Individualised educational paths, weekly student progress diaries (“Kaizen journals”), knowledge microchecking, and pedagogical time management were major model components. We proposed using interdisciplinary aspects, such as the Fibonacci sequence, to explain protein molecule spatial arrangement, merging biochemistry with arithmetic. Students were given unique autonomous work activities to build modelling, spatial and logical analysis skills. International practices for implementing Kaizen in higher education in Japan, Singapore, and South Korea were analysed to find effective approaches, gamified monitoring tools, mobile applications, and Lean Six Sigma integration for Kazakhstan teacher education.